Lube Oil Wear Reduction via Organic Tribofilms - Ismail, N.A.; Bagheri, S. (MDPI, 2017)
Effective tribofilms are desirable to protect mechanical systems. In the research, the reduction in wear and friction were investigated through the use of organic additives. Graphene-based organic additives were prepared by surface modification of graphene using organic moiety that will provide tribochemical reaction with rubbing metal surface. The role of surface protective additives becomes vital when operating conditions become severe and moving components operate in a boundary lubrication regime. After protecting film is slowly removed by rubbing, it can regenerate through the tribochemical reaction of the additives at the contact. Many researchers demonstrated that organic additives physically or chemically adsorbed on rubbing metal surfaces to form monolayers, with their shear strength deriving primarily from the weak van der Waal interactions between opposing hydrocarbon chains at the interfaces. Experiments were conducted on a base oil where 0.01 wt % of the additive was used. Tribological evaluation was conducted using four-ball tester under room temperature and the morphology of the worn surfaces were characterized using Field emission scanning electron microscopy (FESEM). Experimental results showed a 16% reduction in friction and 30% reduction in wear when compared to the base oil containing no additive.